Enhanced bone mass and physical fitness in prepubescent basketball players - Zribi, A.; Zouch, M.; Chaari, H.; Bouajina, E.; Zouali, M.; Nebigh, A.; Tabka, Z. (Journal of Clinical Densitometry, 2014)
The aim of this study was to examine the effect of basketball practice on bone acquisition in the prepubertal age. In total, 48 prepubescent male basketball players aged 11.1 ± 0.8 yr, Tanner stage 1, were compared with 50 controls matched for age and pubertal stage. Areal bone mineral density, bone mineral content (BMC), and bone area (BA) in deferent sites associated with anthropometric parameters were measured by dual-energy X-ray absorptiometry. Running and jumping tests were performed. Analysis of Student's impaired t-test revealed that basketball players attained better results in all physical fitness tests (p < 0.05). They also exhibited significantly greater BMC and BA in whole body, upper and lower extremities, trochanter, total hip, and whole right and left radius (p < 0.001) compared with the controls. No significant differences were observed between groups in right and left ultradistal and third distal radius and spinal regions, BMC, and BA, whereas a significant positive correlation was reported between lean mass, BMC, and BA of lower limbs. In summary, basketball practice in prepubertal age is associated with improved physical fitness and enhanced lean and bone mass in loaded sites.